Impacts of Climatic Variation on Water Balance and Yield of Watershed (Insights from The Kaduna Watershed, North Central Nigeria) - Toriman Mohd Ekhwan; lam Kuok Choy; Jaafar Mokhtar; Adeyemi Jibrin Alakeji; Japheth Daramola (Faculty of Geography, Universitas Gadjah Mada, 2022)
Many authors have identified climate variation impacts in Nigeria. However, the effects on water balance and water yield have not been thoroughly considered. Good knowledge of water balances is vital for sustainable water resource management in northern Nigeria due to high water stress and increased evapotranspiration compared to another part of the country. Hence, the study presents the first detailed climatic variation impacts on watershed water balance and water yield in north-central Nigeria. Soil and Water Assessment Tool (SWAT) was applied to predict the hydrological procedures. The Kaduna watershed (32,124 km2) calibrated and validated streamflow results were run independently using three land cover maps of 1975, 2000, and 2013. The model performance evaluation was statically attained using the coefficient of determination (r2), Nash-Sutcliffe (NS), besides the percentage of observed data (p-factor). The model evaluation result of r2 (0.80), NS (0.71), and p-factors of 0.86 indicated the model satisfactory performance evaluation of streamflow predictions. The streamflow estimation revealed Threshold depth of water (GWQMN.gw) as the most sensitive parameter. The findings discovered declined between 1975 and 2013 in precipitation, water yield, surface runoff (SURQ_mm), lateral flow (LAT_Qmm), deep aquifer (Deep_mm) by 4.2%, 37.3%, 56%, 15%, and 100% respectively, while shallow groundwater aquifer (GW_Qmm) experienced 10% decrease between 1975 and 2000 and appreciated by 6% between 2000 and 2013, evapotranspiration (ET_mm) increase by about 22.2% between 1975 and 2013. These results suggest considerable effects of climate variation in the watershed and call for further investigation to mitigate climate change influence.